Sinapic-Acid-Loaded Nanoparticles Optimized via Experimental Design Methods: Cytotoxic, Antiapoptotoic, Antiproliferative, and Antioxidant Activity - Poyraz, Fatma Sayan; Akbas, Gulsah; Duranoglu, Dilek; Acar, Serap; Mansuroglu, Banu; Ersoz, Melike (AMER CHEMICAL SOC, 2024)
Nanoparticles are frequently investigated as carrier systems that increase the biological activities of hydrophobic molecules, especially by providing them with water solubility. Sinapic acid (Sa), commonly found in plants, is a phenolic compound with a wide spectrum of biological activities and extensive pharmacological properties. The aim of this study was the synthesis/characterization of optimized sinapic-acid-loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (SaNPs) to improve the solubility of sinapic acid (Sa) that limit its use in the biological system and investigate the biological activities of these nanoparticles in the breast cancer cell line. For this purpose, sinapic-acid-loaded PLGA nanoparticles were obtained and optimized by experimental design methods. Then, cytotoxic (MTT method), antiapoptotic (terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay), antiproliferative (immunocytochemically by PCNA assay), and antioxidant activities (superoxide dismutase (SOD) and catalase activities, glutathione, malondialdehyde (MDA), and caspase-3 levels) of optimized nanoparticles were examined comperatively with free drug on MCF-7 cells. The IC50 values of the SaNPs (170.6 +/- 3.6 nm size) in MCF-7 cells were determined at 180, 168, and 145 mu g/mL for 24, 48, and 72 h, respectively, and at these doses, the nanoparticles did not show any toxic effect on the MCF10A cell line. Treatment of Sa and SaNPs at doses of 24 and 48 h showed a statistically significant reduction in the PCNA level in MCF-7 cells, with an increase in the number of cells leading to apoptosis. In MCF-7 cells treated with SaNP at concentrations of 150 and 200 mu g/mL for 24 h, MDA levels were significantly increased, SOD activities were significantly decreased, and reduced glutathione (GSH) and catalase levels were increased compared with control groups. The findings of this study indicate that polyphenolic compounds can contribute to the design of drugs for treatment by forming nanoparticle formulations. The developed nanoparticle formulation is thought to be a useful model for other hydrophobic biological active substances.
Keywords: PHENOLIC-ACIDS; OXIDATIVE STRESS; HUMAN BREAST; APOPTOSIS; CELLS; PROLIFERATION; MECHANISMS; QUERCETIN; CASPASE-3; TOXICITY; Chemistry